2013
DOI: 10.3390/en6115738
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Adapting Approach for Forecast-Less Scheduling of Electrical Energy Storage Systems in a Liberalized Energy Market

Abstract: Abstract:In this paper, an original scheduling approach for optimal dispatch of electrical Energy Storage Systems (ESS) in modern distribution networks is proposed. The control system is based on fuzzy rules and does not use forecasts since it repairs the past history according to the real time data on the electrical energy cost, renewable energy production and load. When the system detects a worsening of performances, the fuzzy logic rule-based control system self-adapts its membership functions using an econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Uncertainty with the MPC models has also been studied within [19][20][21] and for minimizing operational costs using electric vehicles [22]. It has also been shown that storage control incorporating uncertainty in the electricity market is possible using a receding horizon and no forecasts [23]; the work successfully reduces the impact of prediction errors using a heuristic-based approach. As forecasting on the LV network is difficult, the control of storage will be dependent on the accuracy of the forecast [12,24].…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty with the MPC models has also been studied within [19][20][21] and for minimizing operational costs using electric vehicles [22]. It has also been shown that storage control incorporating uncertainty in the electricity market is possible using a receding horizon and no forecasts [23]; the work successfully reduces the impact of prediction errors using a heuristic-based approach. As forecasting on the LV network is difficult, the control of storage will be dependent on the accuracy of the forecast [12,24].…”
Section: Introductionmentioning
confidence: 99%
“…Scheduling systems developed by Sanseverino et al [61] and Grillo et al [62] depend on price signals over the use of TOU tariffs, day-ahead energy market data, an hour ahead market data, and spot prices optimize the charging and discharging of battery energy storage (BES). Utilization of day-ahead, hour-ahead, and spot price markets provides the scheduling systems a precise image of the load on the grid.…”
Section: Peak Shaving Via Solar Pv-battery Storage Systemmentioning
confidence: 99%
“…The optimized solution using the proposed DOPF is compared to a centralized OPF solution using GSO algorithm as described in [9]. Since the solution of the DOPF is approximated, the attained solution is close to the optimal, but not the optimal.…”
Section: Applicationmentioning
confidence: 99%
“…OPF is essentially a tertiary level optimal operation issue in electric power systems and the latter has been for a long time a concern of many researchers. For this purpose, many optimization techniques have been used, such as "the steepest descent" method [6], particle swarm optimization method [7], Glow-worm Swarm Optimization (GSO) method [8] fuzzy rules method [9,10], dynamic programming [11], global optimization [12,13] and so forth. In addition, optimization problems have been solved considering the presence of energy storage systems, which are critical in islanded MGs systems [10,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%